To find the inverse of the function \( g(x) = -x^2 + 3 \) for \( x \geq 0 \), follow these steps:
-
Replace \( g(x) \) with \( y \): \[ y = -x^2 + 3 \]
-
Swap \( x \) and \( y \) to find the inverse: \[ x = -y^2 + 3 \]
-
Solve for \( y \): \[ -y^2 = x - 3 \ y^2 = 3 - x \ y = \sqrt{3 - x} \quad (\text{since } x \leq 3 \text{ and } y \geq 0) \]
-
Write the inverse function: \[ g^{-1}(x) = \sqrt{3 - x} \]
Thus, the inverse of the function \( g(x) = -x^2 + 3 \) for \( x \geq 0 \) is: \[ g^{-1}(x) = \sqrt{3 - x} \]